AERP Strategy as The Spirit of Clil Approach: One Way Solution To Teach Content Subjects Delivered In English In SBI Program - Unsiah, Frida (Fakultas Ilmu Budaya, Universitas Brawijaya, 2012)
Realizing the importance of English acquisition nowadays, various efforts have been conducted in any aspects of life such as in education field. As stated in the Decree of Minister of Education no 20/30, by applying Internationally Standard Schools program starting from elementary to senior high school levels, it is expected that students who take a part in this program are able to use English as their means of communication both inside and outside the classroom that later, they can compete globally in either national or international level. However, although this program has been conducted for more than five years in Indonesia, it does not show satisfying progress. The evidence shows that the ability of the SBI teachers in English is still below the standard which automatically affects the studentsâ achievement on the subjects delivered in English such as on Math and Science. This paper covers the information on a particular teaching strategy, called as AERP (Activation, Exposure, Repetition, and Production) under the spirit of CLIL (Content and Language Integrated Learning) approach, as the alternative way to teach content subjects delivered in English in SBI program. Expectedly, this paper will provide solutions to solve teaching problems in SBI program.Keywords: SBI program, teaching strategy, CLIL approach, and AERP strategy